Interleukin-1β Promotes Schwann Cells De-Differentiation in Wallerian Degeneration via the c-JUN/AP-1 Pathway - Chen, Gang; Luo, Xiaohe; Wang, Wenjin; Wang, Yimei; Zhu, Fei; Wang, Wei (Frontiers in Cellular Neuroscience, 2019)
Schwann cells (SCs) de-differentiate in Wallerian degeneration (WD) following nerve injury and, by doing so, can actively promote nerve repair and functional recovery. An innate-immune response is an important component of the complex of events referred to as WD. Damaged PNS SCs produce IL-1β and other inflammatory cytokines. We hypothesized that, in addition to a role in immune responses, IL-1β participates in de-differentiation and proliferation of SCs. qPCR and ELISA demonstrated that expression of Il-1β mRNAs and protein increased after nerve injury. Immunofluorescent staining and western blotting demonstrated that expression of the p75 neurotrophin receptor (p75NTR) was significantly increased and levels of myelin protein zero (MPZ) were significantly decreased after IL-1β exposure compared with control groups in vitro WD. Additionally, qPCR demonstrated that IL-1β elevated expression of the de-differentiation gene p75NTR and decreased expression of myelination locus MPZ and promoted SCs de-differentiation. Furthermore, immunofluorescent staining, western blotting, qPCR and ELISA revealed that IL-1β promoted c-JUN expression and activation of AP-1 activity of SCs in an in vitro WD model. Finally, Immunofluorescent staining illustrated that IL-1β elevated expression of Ki67 in Schwann cells nuclei, the apoptosis of Schwann cells were detected by TUNEL. SCs of WD produce IL-1β which promotes SCs de-differentiation and proliferation.